Practice makes perfect (or close enough): Teaching paraphrasing in an undergraduate lab - Donner, Tyler (Canadian Perspectives on Academic Integrity, 2021)
During my time as a lab coordinator for labs of five different undergraduate courses, I have tried many different strategies to reduce incidents of plagiarism in student work. Following a large number of cases (> 50) in the first semester of online lab instruction, I dedicated an entire week of lab activities to teaching and discussing plagiarism, paraphrasing, and citation. In three lab courses at different levels of the undergraduate program, I saw a major reduction in the number of cases of plagiarism detected. In this session, I will share the activity, facilitate discussion about activities that others have implemented in their courses, and discuss how to adapt this activity to other subject areas.